Numerical and Experimental Study of Multi-layer Armors for Personal Protection - Jassem, Ahmed Ehsan; Jawad, Akram Jassim; Samarmad, Ahmed Oleiwi; Hamzah, Ahmed Fadhil (Physics and Chemistry of Solid State, 2022)
Currently, personal armor is considered the basic requirement in combat, especially in the Middle East. The current research attempts to design and manufacture a novel body armor from cheap and available materials. When compared to traditional materials’ body armor, composite ballistic body armor has become a superior alternative for personal protection. In this study, alternative materials were proposed to develop an armor consisting of modified rubber and ebonite, as well as pieces of ceramic from alumina as hexagons shape, Kevlar and Carbon woven, and modern technologies shear thickening fluids. The armor was numerically evaluated using (ANSYS) commercial software using different bullet velocities ranging from (740 to 940) m/s and different numbers of carbon and Kevlar woven soaking shear thickening fluids to reach the best arrangement of layers with the best performance and compare them in the experimental data. The numerical results show the best performance for plate armor consisting of 23-layers, which were then experimentally tested using a weapon type (AK-47) rifle with bullet 7.62*39 mm. The experimental test showed no complete penetration, with a back deformation of 7.5 mm. When the shock of the double bullet into the plate at the same location showed no complete penetration with a back deformation of 11.3 mm, the body armor exhibited superior protective performance and was compatible with standard NIJ Standard-0101.03.